Metz/Divodurum, cité des Médiomatriques : apport de deux fouilles récentes (place de la République et rue Paille-Maille) à la question des origines - Gaël Brkojewitsch; Christian Dreier; Sandrine Marquié (Gallia)
This essay’s aim is to present the current state of knowledge about the origins of the Roman town of Metz/Divodurum. In order to arrive at this, the literary sources and the results of urban archaeological excavations are used. The main research in the urban centre will be described, following a chronological and topographical rationale (Haut de Sainte-Croix hill, Citadelle hill, Outre-Seille area, Pontiffroy). The assumption being that the Roman town grew on the location of the oppidum (Haut de Sainte-Croix hill) with almost no interruption after the La Tène occupation, attention was focused on two areas which have been the object of recent excavations (Place de la République, excavated in 2009, the Citadelle hill and Paille-Maille Street excavated in 2012 in the Pontiffroy area) to offer instances for comparison. The data gathered give an illustration of the different kinds of housing and an evocation of the urban development and of the city’s limits after the Conquest.